Estratégia para a criação de um projeto empreendedor : Consultoria Infra TI - Rodrigues, Marcus Paulo Linares (2018)
The present work was carried out with the objective of designing the business model of an entrepreneurial project dedicated to support services, consulting, information and training in Information Technology (IT) infrastructure. The scope of the business encompasses processes and people development, offering a set of services to the corporate market that provide solutions for cost reduction, productivity and development of personal and organizational skills. The analysis of the scenarios of the environment and research carried out with potential clients subsidized the identification of the necessary structure for the business. We resorted to the support of conceptual and experimental views found in bibliographical sources, as a way of conferring validity to the presented proposal. With knowledge of aspects related to an entrepreneurial project, including issues such as the importance of innovation, the main motivations and competencies needed to undertake and the risks, problems and limitations commonly faced, which resulted in the design of a business model applicable to the use of the opportunity identified, with the definition of structural aspects demanded for it. From the recommendations presented, the planning of the actions to be carried out was carried out, indicating the resources involved. As the enterprise has already begun its operation, some of the proposed actions have already been carried out and others are still in execution. Dedicated to proposing ways to establish favorable conditions for the development and sustainability of an entrepreneurial initiative, the work presents an example that can be replicated in companies that find a similar situation. Thus, in addition to the direct benefits to health and prosperity of the company, the proposed actions tend to influence the development of management technology, as a socioeconomic development agent of the community in which it operates.